Private foundations and development cooperation: insights from Tanzania - Erik Lundsgaarde; Evelyn Funk; Anja Kopyra; Jennifer Richter; Hannah Steinfeldt (Deutsches Institut für Entwicklungspolitik (DIE), 2012)
While the role of private foundations as development assistance providers has attracted growing interest in the development policy community, country-level analyses of foundation engagement remain scarce. This study examines private foundation funding for development in Tanzania, focusing on the priorities and character of foreign foundation activities in the country. Drawing on interviews with foundation representatives, foundation grantees, development partners, government representatives and other stakeholders, this study assesses whether common claims made about foundation work apply in the Tanzanian context. The extent to which foundations support innovation, fill financing gaps, and engage with the government and other aid providers are among the key issues the study considers. Although private foundations do not appear to be very visible at the country level and display numerous similarities with other aid providers, many general claims about foundation engagement in global development resonate in the Tanzanian context.
Keywords: 330; Aufstrebende Mächte; Entwicklungsfinanzierung und öffentliche Finanzen; Entwicklungshilfe; Stiftung; Ausländisch; Entwicklungshilfe; Tansania